RELATIONAL DIALECTICS ON SUNDANESSE-ARABIAN MARRIAGE - Ganiem, Leila Mona (Universitas Prof. Dr. Moestopo (Beragama), 2009)
In a heterogenic country. such as Indonesia, an intercultural marriageis always possible. Many data reveal that intercultural marriages potentially are more troubled than marriages of the same culture. Leslie Baxter and Montgomery s theory ( 1998) on relational dialectics analyzed the strains that are conjoined in a romantic relationship. · Those are internal and external· dialectics. In this research the relational dialectics theory was studied in thecultural context marriages between the Sundanese and Arabs. The aim of the research was to: 1) get the knowledge about internal-external relational dialectics of intercultural couples, 2) get the understanding about the experiences of the couples in connect ion to intercultural dialectics and 3) get the understanding on how those couples overcome the intercultural dialectics they face in their marriage on the internal and external scope. From this research it can be concluded that internal and external dialectics are tended to be sourced by cultural difference of each couple. The most conspicuous dialectics of those couples were caused by the individuals· competence or incompetence to predict their spouses culture or surroundings.